If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 1 = 4x + 2 Reorder the terms: 1 + 6x = 4x + 2 Reorder the terms: 1 + 6x = 2 + 4x Solving 1 + 6x = 2 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 1 + 6x + -4x = 2 + 4x + -4x Combine like terms: 6x + -4x = 2x 1 + 2x = 2 + 4x + -4x Combine like terms: 4x + -4x = 0 1 + 2x = 2 + 0 1 + 2x = 2 Add '-1' to each side of the equation. 1 + -1 + 2x = 2 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 2 + -1 2x = 2 + -1 Combine like terms: 2 + -1 = 1 2x = 1 Divide each side by '2'. x = 0.5 Simplifying x = 0.5
| (p^5/6x)^5 | | 2(7+n)=-10 | | 7x^2+100x-24=0 | | x+7-x=-5 | | x+20=2x+80 | | 45+90x=855 | | 5x+252=14x-9 | | 30-6x=12-8x | | 6t^2=-t+2 | | 7X+3Y+36=0 | | 12m+8-5m+2+m=6(m-1) | | -4x^2+50x-150=0 | | 7x+(7x+1)+(8x+3)=180 | | 0.4x-9.5(x-1)=55 | | 6a+10a^2=0 | | 2(a-7)-3a=-17-(a-3) | | 6x^2+50x+100=0 | | 12s+9t=57 | | 4x+(12)=8 | | 3a-10=25 | | 8(-2m-7)+8(-5+m)=4m-6m | | 3z+2(6-z)=-(z-1)+1 | | 3a-10=-25 | | 28*x=(4x-2)*7 | | 5-8x+x=40 | | d(3d-15)=0 | | Y=.5+8 | | -8m-[2(10-5m)+15]=9m | | 45a^4b^3/15a^4b^2 | | r^2+81=r^2+6r+9 | | 2(7c-1)-18=12c+2 | | 7.4X=-52.54 |